2019
DOI: 10.1021/acsami.9b00476
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic Acid-Functionalized Metal–Organic Frameworks for Sc(III) Selective Adsorption

Abstract: The increasing demand for rare-earth elements (REEs) due to their extensive high-tech applications has encouraged the development of new sustainable approaches for REE recovery and separation. In this work, a series of acrylic acid-functionalized metal−organic framework materials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…4b, Table 2). All the materials had higher selectivity towards Er 3+ than to Gd 3+ and Nd 3+ when compared to recently studied adsorbents (Table 3), such as MOFs [21,[67][68][69], zirconium (IV) organophosphonates [33,35], commercial resins [70], PEI cellulose nanocrystals [71], and competitive with functionalized mesoporous silica KIT-6 [72]. Moreover, MIL-101-T50 shows practically no adsorption of Nd 3+ or Gd 3+ .…”
Section: Selectivity Testsmentioning
confidence: 81%
“…4b, Table 2). All the materials had higher selectivity towards Er 3+ than to Gd 3+ and Nd 3+ when compared to recently studied adsorbents (Table 3), such as MOFs [21,[67][68][69], zirconium (IV) organophosphonates [33,35], commercial resins [70], PEI cellulose nanocrystals [71], and competitive with functionalized mesoporous silica KIT-6 [72]. Moreover, MIL-101-T50 shows practically no adsorption of Nd 3+ or Gd 3+ .…”
Section: Selectivity Testsmentioning
confidence: 81%
“…It was reported that the acidic carboxylic groups of MIL-101 functionalized by acrylic acid participate in adsorption of Sc 3+ ions. The conclusions were made on the basis of the strong decrease in the intensity of the CO band at 1712 cm –1 and the OH band at 3430 cm –1 (associated with the COOH moieties) after adsorption of Sc 3+ …”
Section: Vibrational Spectra Of Mofsmentioning
confidence: 99%
“…The conclusions were made on the basis of the strong decrease in the intensity of the CO band at 1712 cm −1 and the OH band at 3430 cm −1 (associated with the COOH moieties) after adsorption of Sc 3+ . 224 Consider now the materials from the CPO-27 series, also called MOF-74. They attract a great interest as typical representatives of MOFs possessing open metal sites.…”
Section: Vibrational Spectra Of Mofsmentioning
confidence: 99%
“…As depicted in Fig. 1(c), the spectra of O 1s were determined as C-O (532.6 eV) [32] and O-H (531.7 eV) [32]. According to Fig.…”
Section: Characterization Of the Modified Alkaline Ligninmentioning
confidence: 99%